Late Relapse of Henoch-Schönlein Purpura in an Adolescent Presenting as Severe Gastroduodenitis - Rubino, Chiara; Paci, Monica; Resti, Massimo; Lionetti, Paolo; Trapani, Sandra (Frontiers in Pediatrics, 2018)
Henoch-Schönlein purpura is a systemic vasculitis, commonly affecting children. Gastrointestinal manifestations are observed in 50-75% of patients; it is well known they may occur before skin lesions in about 20% of cases during the first vasculitic episode. Relapses occur in about one third of patients, typically within four months from the initial presentation and with milder symptoms. We report the case of a 17-year old girl with an atypical relapse of Henoch-Schönlein purpura, presenting with acute abdominal symptoms five years after the first episode. Esophagogastroduodenoscopy showed duodenal multiple hyperemic and hemorrhagic lesions. To our knowledge this is the first case of hemorrhagic-erosive duodenitis representing a relapse of Henoch-Schönlein purpura occurring several years after the initial episode. Duodenojejunal inflammation should be considered as primary manifestation of Henoch-Schönlein purpura, not only during the first episode, but also in relapses. Endoscopy can be helpful for differential diagnosis, especially in patients with atypical manifestations. Further studies are needed to evaluate risk factors for Henoch-Schönlein purpura recurrence and the possible role of faecal calprotectin as an early marker for gastrointestinal involvement.